Are the States United? - Moro, Sérgio (2022)
Moro, S., Batista, F., Rita, P., Oliveira, C., & Ribeiro, R. (2019). Are the States United? An Analysis of U.S. Hotels’ Offers Through TripAdvisor’s Eyes. Journal of Hospitality and Tourism Research, 43(7), 1112-1129. https://doi.org/10.1177/1096348019854793